An isolated retrograde-perfused newborn mouse heart preparation - Barajas, Matthew (MethodsX, 2020)
The Langendorff-perfused model is a powerful tool to study biological responses in the isolated heart in the absence of confounders. The model has been adapted recently to enable study of the isolated mouse heart and the effects of genetic manipulation. Unfortunately, the small size and fragility of the mouse heart pose significant challenges, limiting application of the Langendorff model to the study of adult mice. Cardiac development is a complex and dynamic process that is incompletely understood. Thus, establishing an isolated-perfused heart model in the newborn mouse would be an important and necessary advance. Here we present a method to successfully cannulate and perfuse the isolated newborn murine heart. We describe the basic and fundamental physiological characteristics of the ex-vivo • The Langendorff model is a powerful tool to study the heart without confounders. • An isolated-perfused newborn murine heart model has yet to be established. • We demonstrate the first successful isolated neonatal murine heart preparation.